Effect of Al on sintering and mechanical properties of WC-Al composites. Issue 15 (15th November 2016) - Shon, In-Jin
Abstract: Effect of Al on mechanical properties, relative densities and microstructures of WC-Al composites was investigated. In the case of cemented WC, Ni or Co is typically added as a binder for the formation of composite structures. However, due to the high cost of Ni or Co and the low corrosion resistance of WC-Ni and WC-Co cermets, interest has been generated in recent years in finding alternative binder phases. In this study, Al was used as a novel binder and was consolidated by the pulsed current activated sintering (PCAS) method. Highly dense WC-Al with a relative density of up to 98% was obtained within 3 min by PCAS under a pressure of 80 MPa. The addition of Al to WC can facilitate consolidation. WC-5 vol% Al has a higher hardness than monolithic WC because of its high relative density and refinement of grain. In addition, the fracture toughness of WC increases with an increase in the addition of Al.